Pengaruh Desain Produk Dan Desain Proses Terhadap Kualitas Produk - Ilham Fadhilah Firdaus; Rita Tri Yusnita; Depy Muhamad Pauzy (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
This study aims to determine and analyze the effect of Product Design and Process Design on Product Quality at PT. Wijaya Agape Tasikmalaya. The research method used is survey, while the type of data used is primary and secondary data. The population in this study are all employees at PT. Wijaya Agape Tasikmalaya numbered 60 people. By taking total/census sampling, the data analysis technique uses path analysis using SPSS software. The results of the study show that good product design has a significant impact on product quality. Aspects such as aesthetics, functionality, and product usability have a positive influence on consumer perceptions of product quality. In addition, effective process design also contributes to product quality. Structured and standardized processes can reduce product defects and improve reliability. This research provides a better understanding of the importance of product design and process design in achieving the desired product quality. The results of this research can be used by companies to improve their design processes and ensure that the resulting products are of good quality. By paying attention to product design and process design holistically, the company can meet customer expectations and maintain a competitive advantage in the market.